Sufficiency and the state: A prospective project - Princen, Thomas (Frontiers in Sustainability, 2022)
Sufficiency as a social organizing principle can be applied to individuals, organizations and economies. But if the encompassing social structure, namely, the state, is still organized around expansionist principles like efficiency and growth, the outcome will be the same—excess, the exceeding of regenerative capacities biophysical and social, local to global. A prospective project of effecting fundamental social change argues that sufficiency must be applied to the state. From a natural resources perspective defining features of the state form are concentration and surplus both of which tend to excess and require endless frontiers. Re-organizing to counter this tendency and institutionalizing sufficiency requires an imaginative politics. A long multicultural human history of reorganizing to adapt to environmental conditions bodes well. Resistance, though, even as the contradictions play out, is to be expected.